PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012 – 2016 - Iqbal Maulana Tofani ; Dra. Wiwik Hidajah Ekowati, M.Si., Ak., CA (Akuntansi FEB - UB, 2018)
Earnings changes obtained by the company in the future cannot be ascertained whether there is an increase or decrease. So it is necessary to make predictions and analyzes related to earnings changes. The analytical used is financial ratio. The aim of this study examines the effect of Current Ratio, Total Debt to Total Asset, Debt to Equity Ratio, Total Asset Turnover, Inventory Turnover, Gross Profit Margin, Net Profit Margin and Operating Profit Margin on earnings changes. The sample of this study is manufacturing companies listed on Indonesia Stock Exchange for the period 2012 to 2016. As many as 58 companies were obtained using purposive sampling technique. The results from the analysis using multiple linear regression show that Current Ratio, Total Asset Turnover, Gross Profit Margin, Net Profit Margin and Operating Profit Margin positively influence earnings changes. While Total Debt to Total Asset, Debt to Equity Ratio and Inventory Turnover does not influence earnings changes. The results of this study provide evidence that the five financial ratios, namely Current Ratio, Total Asset Turnover, Inventory Turnover, Gross Profit Margin, Net Profit Margin and Operating Profit Margin can be used as predictions related to earnings changes by the company. Keyword: Current Ratio, Total Debt to Total Asset, Debt to Equity Ratio, Total Asset Turnover, Inventory Turnover, Gross Profit Margin, Net Profit Margin, Operating Profit Margin, earnings changes